Depression, anxiety and their comorbidity in the Swedish general population: point prevalence and the effect on health-related quality of life - Johansson, Robert; Carlbring, Per; Heedman, Åsa; Paxling, Björn; Andersson, Gerhard (PeerJ (San Francisco, CA), 2013)
Background. Depression and anxiety disorders are major world-wide problems. There are no or few epidemiological studies investigating the prevalence of depression, generalized anxiety disorder and anxiety disorders in general in the Swedish population. Methods. Data were obtained by means of a postal survey administered to 3001 randomly selected adults. After two reminders response rate was 44.3%. Measures of depression and general anxiety were the 9-item Patient Health Questionnaire Depression Scale (PHQ-9) and the 7-item Generalized Anxiety Disorder Scale (GAD-7). The PHQ-9 identified participants who had experienced clinically significant depression (PHQ-9 ≥ 10), and who had a diagnosis of major depression (defined by using a PHQ-9 scoring algorithm). Clinically significant anxiety was defined as having a GAD-7 score ≥ 8. To specifically measure generalized anxiety disorder, the Generalized Anxiety Disorder Questionnaire-IV (GAD-Q-IV) was used with an established cut-off. Health-related quality of life was measured using the EuroQol (EQ-5D). Experiences of treatments for psychiatric disorders were also assessed. Results. Around 17.2% (95% CI: 15.1-19.4) of the participants were experiencing clinically significant depression (10.8%; 95% CI: 9.1-12.5) and clinically significant anxiety (14.7%; 95% CI: 12.7-16.6). Among participants with either clinically significant depression or anxiety, nearly 50% had comorbid disorders. The point prevalence of major depression was 5.2% (95% CI: 4.0-6.5), and 8.8% (95% CI: 7.3-10.4) had GAD. Among those with either of these disorders, 28.2% had comorbid depression and GAD. There were, generally, significant gender differences, with more women having a disorder compared to men. Among those with depression or anxiety, only between half and two thirds had any treatment experience. Comorbidity was associated with higher symptom severity and lower health-related quality of life. Conclusions. Epidemiological data from the Swedish community collected in this study provide point prevalence rates of depression, anxiety disorders and their comorbidity. These conditions were shown in this study to be undertreated and associated with lower quality of life, that need further efforts regarding preventive and treatment interventions.